LOCAL MARINE RESERVOIR AGE (ΔR) RECONSTRUCTED BASED ON THE TSUNAMI DEPOSIT FROM PANGANI BAY (TANZANIA). Issue 4 (29th August 2021) - Soulet, Guillaume; Maselli, Vittorio
ABSTRACT: Quantifying the local marine reservoir age (ΔR) and its change over time is critical for precise radiocarbon calibration of marine samples and for the study of the ocean carbon cycle. ΔR values are scarce for the African coast facing the Indian Ocean, and the few values available were obtained from pre-bomb shells collected during the 19th century. Here, the ΔR value for calibrated year 1110 ± 25 (1σ) CE was reconstructed from radiocarbon dating and Bayesian analysis of marine and terrestrial materials coexisting in a tsunami deposit discovered in Pangani Bay (Tanzania, western Indian Ocean coast). The reconstructed ΔR of –8 ± 40 (1σ, n = 3) is similar to pre-bomb regional estimates and provides new information to investigate regional ΔR change over time. The Bayesian analysis of the dated samples revises the age of the tsunami event found in Pangani Bay to 1064–1157 cal CE (95.4% confidence level) or 1110 ± 25 (1σ) cal CE, about one century younger compared to the previous estimate. Our results indicate that the new ΔR value and the proposed calibration approach can be used to refine existing chronologies in the region, with implications for paleo-environmental reconstructions and archaeological studies of Early Swahili societies.